1989
DOI: 10.1016/s0886-3350(89)80011-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual results following vitreous loss and primary lens implantation

Abstract: Implantation of an intraocular lens following vitreous loss at cataract surgery is a controversial decision. To address this issue, we retrospectively identified all cases performed at the University of Minnesota in the last three years that had either a posterior or an anterior chamber lens placed following anterior vitrectomy. Twenty patients had a posterior chamber lens implant; 14 had follow-up longer than six months. All these patients achieved 20/40 or better visual acuity, although one patient had a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Not surprisingly, this study confirmed that capsular tears are more common than capsular dialyseswith incidences (25) Primary procedure -AC IOL implanted 4 (9) Primary procedureno IOL implanted 3 (7) Secondary procedure -AC IOL implanted 2 (5) AC IOL (total of primary and secondary procedures) 6 (14) PC=posterior chamber; AC=anterior chamber.…”
Section: Resultssupporting
confidence: 73%
“…Not surprisingly, this study confirmed that capsular tears are more common than capsular dialyseswith incidences (25) Primary procedure -AC IOL implanted 4 (9) Primary procedureno IOL implanted 3 (7) Secondary procedure -AC IOL implanted 2 (5) AC IOL (total of primary and secondary procedures) 6 (14) PC=posterior chamber; AC=anterior chamber.…”
Section: Resultssupporting
confidence: 73%
“…[1][2][3][4][5] However, conflicting results are observed in the literature regarding the effect of vitreous loss and postoperative VA. Some studies show no significant difference in postoperative VA for surgeries complicated with and without vitreous loss, while others show a decrease in postoperative VA. [5][6][7] In this study, we observe that vitreous loss is a risk factor for decreased postoperative VA regardless of a vitrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…This poorer vision could be due to a complication such as cystoid macular edema occurring as a result of an 'incomplete vitrectomy,' a procedure characterized by the unintentional retention of vitreous due to surgical error. 4,5 Also, it has been shown that excessive surgical manipulations cause more complications, which in turn can lead to a poorer visual prognosis. For example, when a vitrectomy has to be performed, the patient is immediately placed at risk for a lower postoperative VA. 1,6 The pre-existing pathology of glaucoma is known to complicate cataract procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighty-nine per cent achieved a VA of 20/40 or better; however, no analysis of subgroups or controls was presented. Spigelman et al 4 reported a 'favourable' visual outcome following vitreous loss but 20 out of their 26 cases were managed by PCL implants. The variation in these results is likely to be due to small case numbers and the different types of salvage procedure adopted.…”
Section: Discussionmentioning
confidence: 99%